Maintenance of Acehnese terms of address in an intermarriage family - Maria Ulfa (Universitas Syiah Kuala, 2017)
This study deals with the maintenance of terms of address of Acehnese young generation in intermarriage family. It employs a qualitative research design with a case study. This study aims to describe: (1) the factors that influence the Acehnese young generation in intermarriage families in maintaining Acehnese terms of address in their family, (2) the patterns of the maintenance of terms of address of Acehnese young generation in intermarriage families, and (3) the reasons why the Acehnese young generation from intermarriage families maintain the terms of address in Acehnese. The subjects were 20 children of intermarriage families, with ages ranging from 15 to 26. The instruments used in this study were a questionnaire and interviews. The results showed that there were 14 respondents (70%) who maintained the terms of address and six (30%) who shifted the terms of address. Moreover, four factors that influenced the younger generation to maintain the terms of address are parental roles, attitudes, environment and demography. Additionally, there were four patterns of the maintenance of terms of address: (1) children of Acehnese fathers maintaining the terms of address, (2) children of Acehnese mothers maintaining the terms of address, (3) children of Acehnese fathers partly maintaining the terms of address mixing Acehnese and Indonesian terms of addresses, and 4) children of Acehnese mothers partly maintaining the terms of address, mixing Acehnese and Indonesian terms of addresses. Finally, three reasons for the maintenance of terms of address are family traditions, ethnic identity and politeness in language.